2009
DOI: 10.3341/kjo.2009.23.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer Thickness Change After Panretinal Photocoagulation in Patients With Diabetic Retinopathy

Abstract: PurposeTo examine the effect of panretinal photocoagulation (PRP) on the retinal nerve fiber layer (RNFL) thickness in patients with diabetic retinopathy.MethodsSubjects included 118 eyes for a treatment group and 164 eyes for a control group. The peripapillary RNFL thickness was measured before and 6 months after PRP in treatment group. In control group, the peripapillary RNFL thickness was measured at baseline and 6 months later. The relationships between changes in RNFL thickness and the number of laser bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 9 publications
3
35
1
Order By: Relevance
“…Unlike this, no significant reductions in nerve fibre layer thickness were observed at 6 months in non-proliferative DR without laser treatment. 20 Diabetic patients may have sub-clinical, underlying visual field defects secondary to pre-existing severe non-proliferative DR or PDR. 22 Laser treatment for PDR induces visual field defects as the ETDRS reported significant worsening and constriction of the visual field at 4 months after full, scatter PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike this, no significant reductions in nerve fibre layer thickness were observed at 6 months in non-proliferative DR without laser treatment. 20 Diabetic patients may have sub-clinical, underlying visual field defects secondary to pre-existing severe non-proliferative DR or PDR. 22 Laser treatment for PDR induces visual field defects as the ETDRS reported significant worsening and constriction of the visual field at 4 months after full, scatter PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Transient thickening post-PRP with the conventional argon laser has also been described by many authors (Kim & Cho 2009). However, the effect of PASCAL on peripapillary RNFL thickness has not been well described.…”
Section: Introductionmentioning
confidence: 84%
“…High powered lasers cause transmission of heat to adjacent tissue causing destructive effects and inflammatory response immediately after laser treatment. This transmitted effect predisposes patients not only to macular edema due to transient choroidal thickening, but, in the long run, increases the risk of developing epiretinal membranes (Kim & Cho 2009). Moreover, the end point laser marks tend to exaggerate with time, which correlates well with reported histological data (Maeshima et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, ONHs in eyes treated with PRP are more likely to be graded as abnormal, but their appearance is not necessarily glaucomatous and may be related to thinning of the RNFL [10]. In contrast, Kim et al concluded that there was no detectable change to the optic nerve following PRP [18].…”
Section: Introductionmentioning
confidence: 90%